Quality-equivalent and cost adjusted measurement of international competitiveness in Japanese rice markets - Ito, Shoichi; Rosegrant, Mark W.; Agcaoili-Sombilla, Mercedita C. (International Food Policy Research Institute, 1995)
In this research, the quality of foreign japonica rices was evaluated in terms of prices relative to Japanese domestic retail prices. Then, retail prices, consumer benefit, and competitiveness among the foreign rices in the Japanese market were estimated assuming those rices were imported at prices based on their production and transportation costs. According to the results, rices produced in China are quite superior to rices grown in the United States. Further, a 700 percent of tariff, which was discussed in the GATT negotiation and assumed to be imposed on rices imported to Japan, appears to be too low for Chinese rices and too high for American rices.